Increased ApoE Expression in Follicular Fluid and the ApoE Genotype Are Associated With Endometriosis in Chinese Women - Liu, Ya-Jing; Xing, Fen; Zong, Kai; Wang, Meng-Yao; Ji, Dong-Mei; Zhao, Yu-Hang; Xia, Yun-He; Wang, An; Shi, Ling-Ge; Ding, Si-Min; Wei, Zhao-Lian; Qiao, Jin-Ping; et al. (Frontiers in Endocrinology, 2021)
More than 10% of women suffer from endometriosis (EMT) during their reproductive years. EMT can cause pain and infertility and requires further study from multiple perspectives. Previous reports have indicated that an increase in apolipoprotein E (ApoE) may be associated with a lower number of retrieved mature oocytes in older women, and an association between ApoE and spontaneous pregnancy loss may exist in patients with EMT. The purpose of this study was to investigate the existence an increase in ApoE in follicular fluid (FF) and the possible relationship between ApoE and EMT in Chinese women. In the current study, 217 Chinese women (111 control subjects and 106 EMT patients) were included. The ApoE genotypes were identified by Sanger sequencing. We found that ApoE expression in FF was higher in patients with EMT than in the control group. In addition, a significant difference in ApoE4 carriers (ε3/ε4, ε4/ε4) was found between the control subjects and the patients with EMT. Furthermore, a nonparametric test revealed significant differences in the numbers of blastocysts and high-quality blastocysts, but not the hormone levels of FSH, LH and E2, between the two groups. We also established a multifactor (BMI, high-quality blastocysts, and ε4) prediction model with good sensitivity for identifying patients who may suffer from EMT. Our results demonstrate that ApoE expression in FF is increased in EMT, the ApoE-ε4 allele is significantly linked to EMT, and a combined analysis of three factors (BMI, high-quality blastocysts, and ε4) could be used as a predictor of EMT.